Sexual Violence and Criminal Law: On Contemporary Problems in the Interpretation of the Rape Offence in the Peruvian Criminal Code - Rodríguez Vásquez, Julio Alberto (2023)
This paper identifies the interpretative and qualification legal problems posed by the criminalisation of rape offences in Peru by examining the most contemporary case law and specialised literature. Through a teleological and systematic legal interpretation of these offences and applying a gender perspective, preliminary alternative solutions are constructed. The main legal conclusion reached is that, with the incorporation of the modality of “taking advantage of any other environment that prevents the person from giving free consent” in the offence of rape in its basic modality (article 170 of the Criminal Code), the Peruvian legal system has incorporated a model based mainly on the absence of consent for sex offences. This model, in turn, is close to the “yes means yes” approach to consent, based on a conventional, constitutional and teleological interpretation of the wording of the criminal offence. This paper also reaches other important legal conclusions about the criminal offence of rape, such as the feasibility of its coverage of cases of stealthing, the legal viability of its commission by compenetration and not only penetration, by improper omission and without requiring lewd intent in addition to regular intent, among others. Finally, considering these conclusions, articles 171, 172, 173, 174 and 175 of the Peruvian Criminal Code are systematically examined and congruent legal interpretations are proposed. One of the most relevant is the unconstitutionality of the criminal offence of rape by deception (article 175) and the rationale for its redirection to article 170, as the former could be used to argue that deception is not a suitable modality for committing rape against an adult or adolescent victim over the age of 13, preventing the adequate protection of sexual autonomy.